2014
DOI: 10.1016/j.molmet.2013.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Opening of the mitochondrial permeability transition pore links mitochondrial dysfunction to insulin resistance in skeletal muscle

Abstract: Insulin resistance is associated with mitochondrial dysfunction, but the mechanism by which mitochondria inhibit insulin-stimulated glucose uptake into the cytoplasm is unclear. The mitochondrial permeability transition pore (mPTP) is a protein complex that facilitates the exchange of molecules between the mitochondrial matrix and cytoplasm, and opening of the mPTP occurs in response to physiological stressors that are associated with insulin resistance. In this study, we investigated whether mPTP opening prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
86
2
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(94 citation statements)
references
References 58 publications
4
86
2
2
Order By: Relevance
“…Perturbation in intracellular Ca 2+ homeostasis resulting from decreased expression/ activity of sarco/ER calcium ATPase (SERCA) and compromised mitochondrial Ca 2+ handling in STZ-induced diabetic hearts ( 76 ) can potentially modulate ceramide metabolism. However, variations in activity of SERCA and mitochondrial Ca 2+ controlling mPTP opening/closure do not affect the levels of diacylglycerol or ceramide ( 77,78 ). This suggests that deregulation of Ca 2+ homeostasis and mPTP activity is likely downstream of ceramide metabolism, or they are independent factors.…”
Section: Lactosylceramide Suppresses Mitochondrial Respiration and Dementioning
confidence: 99%
“…Perturbation in intracellular Ca 2+ homeostasis resulting from decreased expression/ activity of sarco/ER calcium ATPase (SERCA) and compromised mitochondrial Ca 2+ handling in STZ-induced diabetic hearts ( 76 ) can potentially modulate ceramide metabolism. However, variations in activity of SERCA and mitochondrial Ca 2+ controlling mPTP opening/closure do not affect the levels of diacylglycerol or ceramide ( 77,78 ). This suggests that deregulation of Ca 2+ homeostasis and mPTP activity is likely downstream of ceramide metabolism, or they are independent factors.…”
Section: Lactosylceramide Suppresses Mitochondrial Respiration and Dementioning
confidence: 99%
“…A link between MPT pore opening and mitochondrial dysfunction and IR was demonstrated by inhibiting in vivo and in vitro the protein cyclophilin D (CypD) that regulates MTP pore opening by directly binding to pore constituent proteins (Taddeo et al 2014). Indeed, mice lacking CypD were protected from high-fat diet-induced glucose intolerance due to increased glucose uptake in skeletal muscle.…”
Section: Mitochondrial Dysfunction and Oxidant Productionmentioning
confidence: 99%
“…Indeed, mice lacking CypD were protected from high-fat diet-induced glucose intolerance due to increased glucose uptake in skeletal muscle. Furthermore, in in vitro models of skeletal muscle IR, it was observed that pharmacological inhibition of MTP pore opening with the CypD inhibitor cyclosporine A prevented IR at the level of insulinstimulated GLUT4 translocation to the plasma membrane (Taddeo et al 2014).…”
Section: Mitochondrial Dysfunction and Oxidant Productionmentioning
confidence: 99%
“…These data suggest that airway epithelial mitochondrial dysfunction may contribute to allergic asthma, even in lean individuals. Mitochondrial dysfunction is a characteristic of obesity, and many studies, particularly in liver and muscle cells, suggest that obesity increases mitochondrial oxidative stress (55,56). Interestingly, airway mitochondria are altered in animals fed a high-fat diet (33).…”
Section: Pre-existing Asthma Complicated By Obesitymentioning
confidence: 99%